1998
DOI: 10.2307/3434094
|View full text |Cite
|
Sign up to set email alerts
|

Variability of House Dust Mite Allergen Exposure in Dwellings

Abstract: Tlhe variability of repeated house dust mite (HDM) allergen determinations at the same site within 3-24 months was evaluated on previously collected samples. Between two and four repeated measurements of Der p 1, a major allergen of Dermatophagoidespteronyssinus and Der f 1, a major allergen of D. farinae, on 46 carpets and 31 mattresses were analyzed. In 90% of carpets and mattresses, HDM allergen concentrations were cinically relevant (at least one measurement >0.1 pg Der p 1 + Der f l/g dust). The coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
(7 reference statements)
1
11
1
Order By: Relevance
“…Repeated measurements of Der p 1 and Der f 1 in 91 children's mattress dust showed generally higher correlations (0.76-0.95) compared with this study on floor dust measurements, but the reported correlation coefficient for Der f 1 was consistent with our study and higher than Der p 1 correlation (Peterson et al, 1999). Another study in Germany by Hirsch et al (1998) showed only a weak correlation between two and four repeated measurements of Der p 1 and Der f 1 on carpets (n ÂŒ 46) and mattresses (n ÂŒ 31). The authors concluded that single observations of dust mite allergens in house dust give only limited information about long-term exposure.…”
Section: Associations Between First and Second Measurementsmentioning
confidence: 92%
See 3 more Smart Citations
“…Repeated measurements of Der p 1 and Der f 1 in 91 children's mattress dust showed generally higher correlations (0.76-0.95) compared with this study on floor dust measurements, but the reported correlation coefficient for Der f 1 was consistent with our study and higher than Der p 1 correlation (Peterson et al, 1999). Another study in Germany by Hirsch et al (1998) showed only a weak correlation between two and four repeated measurements of Der p 1 and Der f 1 on carpets (n ÂŒ 46) and mattresses (n ÂŒ 31). The authors concluded that single observations of dust mite allergens in house dust give only limited information about long-term exposure.…”
Section: Associations Between First and Second Measurementsmentioning
confidence: 92%
“…Allergen concentration and total mold spore counts The seasonal variation of allergen and mold concentrations in different climates has been discussed in detail in the literature, indicating allergen-specific seasonalities (Platts-Mills et al, 1987;Lintner and Brame, 1993;Munir et al, 1993;ChanYeung et al, 1995;Marks et al, 1995;Miyazawa and Suzuki, 1996;Hirsch et al, 1998;Koch et al, 2000;Chew et al, 2001;Su et al, 2001).…”
Section: Seasonal Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it is well established that HDM allergen levels can vary over time and during different seasons (32,33). We observed a 4-to 8-fold reduction in pretreatment allergen concentrations after interventions in homes enrolled between July-March and followed for 8 weeks.…”
Section: Discussionmentioning
confidence: 53%